UJI SENSITIVITAS BAKTERI TAHAN LOGAM BERAT PADA PERAIRAN SUNGAI DRIYOREJO GRESIK - Nurul Avidhah Elhany; Uni baroroh husnudin (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2022)
Heavy metal pollution is one of the problems that arise because of the large number of industrial wastes containing heavy metals. Efforts to control waste, especially heavy metals in waters need to be carried out immediately, because heavy metals, such as lead (Pb) and chromium (Cr) are toxic to humans. One way that can be done is by doing biomonitoring. Microbes can be used as bioindicators of the presence of pollutants/waste in waters. Microbes utilize organic, inorganic, and metallic wastes as substrates for their growth. The sensitivity test of Pb and Cr heavy metal-resistant microbes was carried out using the paper disc method. Paper discs with various concentrations of heavy metals Pb and Cr were placed in such a way on the surface of NA media that had been inoculated with Pb and Cr heavy metal-resistant microbial isolates. Incubated for 24 hours and measured the inhibition zone. The results showed that 3 heavy metal resistant bacteria were K1 (Pseudomonas pseudomallei), K2 (Pseudomonas fluorescens), and K3 (Bacillus subtilis). Overall, none of the inhibition zones exceeded 0.50 mm and this indicated that the sensitivity of the three bacteria to heavy metals Pb and Cr was low. They are can be used as bioindicators of the presence of heavy metals Pb and Cr because they are able to grow in an environment with heavy metal concentrations of Pb and Cr above the threshold. K1 (Pseudomonas pseudomallei), K2 (Pseudomonas fluorescens), and K3 (Bacillus subtilis) have potential as bioremoval agents for heavy metals Pb and Cr.